Synthesis and Biological Evaluation of Novel Aromatic Imide-Polyamine Conjugates - Ming Li; Yuxia Wang; Jianying Zhang; Songqiang Xie; Chaojie Wang; Yingliang Wu (Molecules, 2016)
Three types of conjugates in which aromatic imide scaffolds were coupled to diverse amine/polyamine motifs were synthesized, and their antitumor activities were evaluated in vitro and in vivo. Results showed that the conjugate 11e of 1,8-naphthilimide with spermine had pronounced effects on inhibiting tumor cell proliferation and inducing tumor cell apoptosis via ROS-mediated mitochondrial pathway. The in vivo assays on three H22 tumor transplant models revealed that compound 11e exerted potent ability in preventing lung cancer metastasis and extending lifespan. Furthermore, the efficacy of 11e in inhibiting tumor growth and improving body weight index were better than that of positive control, amonafide. Our study demonstrates that compound 11e is a valuable lead compound for further investigation.